Combustion Analysis of Biodiesel Derived from Bone Marrow in a Diesel Generator at Low Loads - (:unkn) unknown (My University, 2019)
In this study, biodiesel was produced from bone marrow by transesterificationmethod. The vast majority of animal bones cannot be collected and recycled.This experimental study was carried out to incorporate unused resources in theeconomy. In this study, the effects of biodiesel produced from bone marrow oncombustion characteristics of diesel engine were investigated. The B20(mixing 20% of biodiesel and 80% diesel) and diesel (D2) were used as fuel inthe tests. The tests were carried out at constant speed (1500 rpm) and differentengine loads (20% and 40% of the maximum power output) of a diesel enginewith direct injection, four-cylinder, and four-stroke. The combustioncharacteristics of the engine, such as cylinder gas pressure, heat release rate,cumulative heat release, and mean gas temperature were determined usingcombustion analysis software (FEBRIS) under 3.6 and 7.2 kW loads. Themaximum points of cylinder gas pressures have been very close in both fuels(D2, B20) at the 3.6 kW power output. The peak pressure of the B20 raisedwith the increase of the engine load. The oxygen in the content and highercetane number of the biodiesel has raised the peak point of the heat release rate.
Keywords: Mühendislik, Elektrik ve Elektronik; Mühendislik, Makine; Malzeme Bilimleri, Kaplamalar ve Filmler; Metalürji Mühendisliği